Testicular function and hormonal regulation in fishes - Nobrega, Rafael Henrique [UNESP]; Lareyre, Jean-Jacques (Elsevier, 2024)
This chapter summarizes our current understanding of teleost testicular and accessory structure function and their endocrine and paracrine regulation. We review recent work on structure and function, especially with respect to the role of endocrine, paracrine, and autocrine players controlling spermatogenesis, focusing on the spermatogonial phase. Our review highlights how much teleost diversity remains effectively unexplored with respect to hormonal regulation of testicular function. We also introduce some examples of within-species variation in male reproductive biology. Future study of such species holds great promise for increasing our understanding of testicular function in general. Throughout, we identify what we consider fruitful avenues for future research, especially those questions where advances in molecular techniques, such as genome editing and single-cell RNA sequencing should now allow progress that was not possible in the past.
Keywords: 11-Ketotestosterone; Accessory gonadal structures; Cortisol; Estradiol; Progestogens; Spermatogenesis; Spermiation; Teleost; Testes; Testosterone